(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
The purpose of this research is to determine the motivation impact of village government apparatus in Wasian village of Dimembe district of North Minahasa Regency. This study uses a descriptive-qualitative approach method. Work motivation is seen from the sixdimensional work motivation of Hezberg. The research informant of the village head, village secretary, head of affairs, and the Dusun/guard heads. Data collection uses interview guidelines, while the analytical techniques used are interactive model analyses of Miles and Hubernann. Based on the results of the study concluded: 1. The motivation of the government apparatus of Walian village is generally still less maximum. Acceptable allowances have not been able to realize the high working motivation among village government officials. 2. The motivation of the village government apparatus to achieve high achievement is still lacking/low. The village apparatus works as it is without pursuing achievements. 3. Motivation to work the village government apparatus to gain recognition of the results of work is still lacking/lower. The village apparatus works as it is and does not think of recognition of the results of work/achievement. 4. Motivation to work the village government apparatus to get a task whose responsibility is greater still less/lower. 5. Motivation for the work of village government apparatus to gain progress on the results of the work is still low. The village government apparatus only works according to existing assignments, and does not work to pursue progress. 6. The motivation to work the village government apparatus to gain the opportunity to develop knowledge and skills in the implementation of tasks is also low, because the opportunity for it is also very rare Keywords: Work motivation, village government apparatus